Numerical study of the airflow structures in an idealized mouth-throat under light and heavy breathing intensities using large eddy simulation - Cui, Xinguang; Wu, Wenwang; Gutheil, Eva (Respiratory physiology & neurobiology, 2018)
An excellent understanding of the airﬂow structures is critical to enhance the eﬃciency of drug delivery via the human oral airway. The present paper investigates the characteristics of both steady and unsteady airﬂow structures in an idealized mouth-throat using large eddy simulation (LES). Representative inhalation ﬂow rates of 15 L/min at rest and 60 L/min in exercise are considered. The study shows that there are more secondary vortices in the pharynx and the laryngeal jet is much longer and more concave in the steady ﬂow ﬁeld at 15 L/ min compared to the higher inspiration rate, which decreases the possibility of drug impinging on the wall. In contrast, the laryngeal jet is much more unsteady at heavy breathing and its strong interaction with the recirculation zone in the trachea leads to a enlarged mixing zone, increasing the possibility for carrying the particles from the laryngeal jet into the recirculation zone, which will lead to a longer residence time of the particles in the trachea and this increases the possibility of drug deposition in this area. In addition, the recirculation zone size is larger, the separation region is far away from glottis, and the reversed ﬂow is slower at light compared to heavy breathing. In conclusion, these airﬂow structures show distinct properties at light and heavy breathing conditions, particularly in the unsteady ﬂow ﬁeld. The study provides evidence about the physical processes leading to both enlarged mixing zones and recirculation zones. It is known that stronger secondary vortices, a stronger laryngeal jet and enlarged recirculation zones deﬁnitely increase the particle deposition in the upper airway. The present paper aims to uncover the physical properties of the airﬂow for diﬀerent breathing conditions, and their detailed eﬀect on particle deposition will be studied in future.
Published online: 08 November 2017
Gesehen am 18.04.2018